Home and work : negotiating boundaries through everyday life - Nippert-Eng, Christina E. (University of Chicago P. ChicagoUS, 1996)
Introduces the concept of boundary work and shows how individuals establish boundaries between home and work by separating objects, people, activities etc. into either category. Looks at transformational activities e.g. commutes and phone calls, changing clothes, hellos and goodbyes etc., all of which serve as integrators as individuals shift from home to work to home. Examines home and workplace related constraints which encourage varying degrees of boundary setting.